Analisis Teori Legitimasi Pada Konflik Rekognisi Penguasaan Tanah Adat antara PT Asam Jawa dengan Komunitas Terdampak - Hayati Harahap, Rahma Hayati Harahap; Nahwa Zainab Marpaung (Jurnal Kajian Agraria dan Kedaulatan Pangan (JKAKP), 2023)
Agrarian conflicts in the plantation sector are dominated by oil palm plantation conflicts. This article discusses the conflict over recognition of customary land tenure that occurred in Torgamba District involving PT Asam Jawa and affected communities. The theory used to analyze the conflict of recognition of customary land tenure is the theory of legitimacy. The method used is the study of literature and literature. Data collection techniques are carried out through scientific journals and other literature sources related to studies and research problems. The results showed that there was a legitimacy gap that occurred between PT Asam Jawa and the affected communities. The legitimacy gap is caused by PT Asam Jawa's failure to meet the needs and expectations of the community and comply with norms, values, and boundaries recognized by local residents.